The Effect of Sustainable Finance on Financial Performance and Asset Quality through Risk Management in Islamic Banks in Indonesia - Agus Windiarto; Susy Muchtar; Tatik Mariyanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This research is driven by the growing focus on sustainable finance rooted in Environmental, Social, and Governance (ESG) principles within the Islamic banking sector, although its application in Indonesia is still not optimal. This study aims to examine the impact of sustainable finance on financial performance and asset quality, considering the mediating influence of risk management in Islamic commercial banks in Indonesia. The research utilizes a quantitative method with a causal framework, utilizing panel data from 12 banks during the period 2021–2024, assessed through panel regression and mediation analysis. The findings indicate that sustainable finance has a significant negative effect on financial performance and no significant effect on asset quality. Furthermore, risk management positively and significantly influences financial performance, while its effect on asset quality is not significant. Moreover, it has been observed that risk management plays a mediating role in the connection between sustainable finance and financial performance, yet not in the link between sustainable finance and asset quality. These results suggest that the effect of sustainable finance is indirect and prolonged by enhancing risk management. This study suggests that Islamic banks must better incorporate ESG principles into their risk management frameworks, and regulators ought to enhance supportive policies.